Heritage and religion in East Asia - Wang, Shu-Li ca. 20./21. Jh.; Rowlands, Michael ca. 20./21. Jh.; Zhu, Yujie (Routledge research on museums and heritage in Asia, 2021)
Recognition and remembrance in religion and heritage -- Modernizing heritage -- From heritage to religion -- Authenticity and sacred.